2017
DOI: 10.1080/14756366.2017.1344236
|View full text |Cite
|
Sign up to set email alerts
|

Primary mono- and bis-sulfonamides obtained via regiospecific sulfochlorination of N-arylpyrazoles: inhibition profile against a panel of human carbonic anhydrases

Abstract: A diverse set of mono- and bis-sulfonamide was obtained via a direct, chemoselective sulfochlorination of readily available yet hitherto unexplored N-arylpyrazole template. Biochemical profiling of compounds thus obtained against a panel of human carbonic anhydrases ( h CA I, h CA II, h CA IV and h CA VII) revealed a number of leads that are promising from the isoform selectivity prospective and exhibit potent inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The inhibition constants were obtained by non-linear least-squares methods using the Cheng-Prusoff equation, as reported earlier 20–24 , and represent the mean from at least three different determinations. All CA isozymes used here were recombinant proteins obtained as reported earlier by our group 10 c, 25 , 26 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition constants were obtained by non-linear least-squares methods using the Cheng-Prusoff equation, as reported earlier 20–24 , and represent the mean from at least three different determinations. All CA isozymes used here were recombinant proteins obtained as reported earlier by our group 10 c, 25 , 26 .…”
Section: Methodsmentioning
confidence: 99%
“…Despite that, all these five membrane-bound isoforms are commonly termed as extracellular CAs due to having their active sites outside the cell. Many sulfonamide-based drugs (Figure 2) such as acetazolamide (AAZ), methazolamide, ethoxzolamide, dorzolamide, brinzolamide, dichlorophenamide, and celecoxib are used clinically for many years as diuretics, anti-epileptics, anti-glaucoma, or as anti-tumor agents 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The lower organic layer was separated, dried over sodium sulfate, and evaporated under vacuum to obtain 3,5-dimethyl-1 H -pyrazolesulfonyl chloride and 1,3,5-trimethyl-1 H -pyrazolesulfonyl chloride (Scheme ). …”
Section: Experimental Conditionsmentioning
confidence: 99%
“…In the recent study performed by Krasavin M. et al a novel series of substituted 1,2,4-oxadiazole-arylsulfonamides has been discovered as selective CA inhibitors with potential application in the cancer therapies [73,74]. An extensive research (conducted by the same research group) exploring various substituted heterocyclic compounds (including 1,3-oxazole, isoxazole, imidazoline and pyrazole) with sulfonamide moiety indicated that 1,2,4-oxadiazol-5-yl-benzene sulfonamides were able to demonstrate extremely high biological activity and selectivity [87][88][89][90]. Inhibitory potency of synthesized compounds was measured with the use of CO 2 hydration stopped-flow biochemical assay against two cytosolic Human Carbonic Anhydrases (hCA I and II) and two membrane-bound cancer related (hCA IX and XII) CA.…”
Section: Cooh Homentioning
confidence: 99%